Study on the Behavior Mechanism of K and Na during the Synthesis of VN Alloy - Lanjie Li; Xindong Wang; Caidong Zhang; Mingliang Lu; Haixu Wang; Heli Wan (Metals, 2022)
In this paper, the sources of K and Na in vanadium-nitrogen (VN) alloys and their effects on the furnace structure were studied. The results show that K and Na are mainly present as counter-ions of decavanadate and dodecanadate in ammonium polyvanadate (APV) and vanadium trioxide (V2O3). In the production process of VN, the concentration of K in the scab produced in the kiln is 25 times higher than that of the vanadium raw material, the concentration of Na is 15 times higher than that of the raw material, and the degree of enrichment of K is stronger than that of Na. Additionally, in the VN products, K and Na are mainly distributed uniformly in the form of KCN and NaCN. The results also found that the K and Na vapors during the production of VN promoted the formation of VN. However, K, Na steam, KCN, NaCN, K2CO3, Na2CO3 and other potassium-sodium high-temperature corrosive substances cause strong corrosion of the furnace lining, graphite sagger, push plate, and heating elements. Therefore, in the process of synthesizing VN, the raw materials of K and Na content of impurity elements must be reasonably controlled. The results not only analyzed the source of K and Na, but also analyzed the characteristics of their enrichment and the influence on the equipment.